(3JGQjN GdESdGe hWHbGJ GdeTGgjQ hGdCYdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3QShd Gddg Udi Gddg Ydjg hSde Edi GdeSLO GdCbUi bGd ehSi Hf YbHI Yf GdRgQi GSQi HQShd Gddg Udi Gddg Ydjg hSde Edi HjJ GdebOS bHd GdgLQI HSfI s
(3BNQgG (B:s
(3GdeGd eGdce hGdYHO YHOce agd YPGHc Yf Gdjhe eUQhb cfgG jhe KOJ eGJcdefG XHi HYSaGf SGLi GdWQa eWQha Je bJd YV Gddg Yfg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs